Science Teachers as Reflective Practitioners at Higher Secondary Level: A Demand for 21st Century Teaching - Farkhanda Tabassum, Qurat-ul-Ain Hina (JSE, 2023)
The study investigated science teachers’ perceptions about the reflective practice at higher secondary with the reference of 21st -century teaching demands. The objectives of the study were: to differentiate science teachers’ attitudes about the reflective practice based on gender at the higher secondary level. The sub-objectives were to differentiate the use of reflective practices on the basis of gender, to differentiate the male and female teachers’ strategies for reflective practice, to distinguish the teachers, professional development on the bases of gender, and the barriers in the use of reflective practice based on gender.